Silymarin: a promising modulator of apoptosis and survival signaling in cancer - Ujjawal Sharma; Praveen Kumar Sahni; Bunty Sharma; Madhu Gupta; Damandeep Kaur; Darin Mansor Mathkor; Shafiul Haque; Sabiha Khatoon; Hardeep Singh Tuli; Astha Mishra; Faraz Ahmad (Discover Oncology)
Abstract Cancer, one of the deadliest diseases, has remained the epicenter of biological research for more than seven decades. Yet all the efforts for a perfect therapeutic cure come with certain limitations. The use of medicinal plants and their phytochemicals as therapeutics has received much attention in recent years. Silymarin, a polyphenolic flavonoid with a variety of anti-cancerous properties, was isolated from the plant Silybum marianum. The present review centres on the function of silymarin in controlling important signalling pathways related to apoptosis and survival, such as the JAK/STAT pathway, PI3K/Akt/mTOR, Bcl-2/Bax, and Fas/FasL. It is emphasised that silymarin's capacity to target these pathways is a key mechanism behind its anticancer effects against a variety of malignancies. By upregulating pro-apoptotic and downregulating anti-apoptotic proteins, silymarin controls a series of events that result in tumor suppression and cell death in a variety of cancer types. The low bioavailability and limited therapeutic efficacy of silymarin are improved by the application of various nano-delivery systems. As efficient carriers, liposomes, polymeric micelles, lipid- and metal-based nanoparticles, increase the solubility and distribution of silymarin in target tissues. Lastly, a number of preclinical studies that provide a basis for upcoming therapeutic interventions are highlighted in the review, providing encouraging directions for additional research and advancement.